Seeing through walls Superman and the science of sight - Biskup, Agnieszka (North Mankato, Minnesota Capstone Press, 2016)
"Explores the real-world science and engineering related to Superman's super-vision"
A gift from book Africa
Science
1 2 13 15
NEW_ZTN_GN
Keywords: Vision -- Juvenile literature; Eye -- Juvenile literature; Superman -- (Fictitious character) -- Juvenile literature